Effectiveness of botulinum toxin injection with and without needle electromyographic guidance for the treatment of spasticity in hemiplegic patients: a randomized controlled trial. (February 2014) - Ploumis, Avraam; Varvarousis, Dimitrios; Konitsiotis, Spyridon; Beris, Alexander
Abstract Purpose: To compare the effects of botulinum toxin injection with and without needle electromyographic guidance for the treatment of spasticity. Method: A randomized controlled study was conducted in a tertiary university hospital. Twenty-seven adult hemiplegic patients with spasticity due to brain or spinal cord damage were included. Spastic muscles were injected with botulinum toxin with or without EMG guidance. The modified Ashworth scale and modified Barthel index in each patient pre- and post-injection were documented. Results: In group A, which consisted of 15 patients (55.55%), the injection was administered with needle electromyographic guidance, while in 12 patients (44.44%) of group B without electromyographic guidance with the use of anatomic landmarks only. The follow-up period was 3 months. At 3 weeks post-injection, spasticity was decreased (p < 0.05) in all patients and the mean (SD) reduction of spasticity was higher (p < 0.05) in group A (1.67 (0.5)) than group B (1.25 (0.46)). Similarly, the mean (SD) functional modified Barthel index improved statistically significantly (p < 0.001) post-injection (45.37 (8.43)) than pre-injection (54.07 (9.610), especially in group A (p < 0.05). Conclusion: The effectiveness of intramuscular botulinum toxin injection for the treatment of spasticity in hemiplegic patients is superior when performed with needle electromyographic guidance than without electromyography. Implications for Rehabilitation It is recommended that botulinum toxin muscle injections of hemiplegic limbs be performed with EMG guidance More spasticity reduction and functional improvement at 3 months post-injection was observed in patients injected with botulinum toxin by the use of combined EMG guidance and anatomic landmarks EMG guidance might also save amount of botulinum toxin due to less spasticity observed during injection than when injection is performed with anatomic landmarks only